The Classical Complement Pathway Is Required to Control Borrelia burgdorferi Levels During Experimental Infection - Zhi, Hui; Xie, Jialei; Skare, Jon T. (Frontiers in Immunology, 2018)
Activation of the classical complement pathway occurs to varying degrees within strains of the Borrelia burgdorferi sensu lato complex, which contain a group of pathogenic spirochetes that cause tick-borne Lyme borreliosis, including the agent of Lyme disease in the United States, Borrelia burgdorferi. Despite this information, details related to the control of Borrelia burgdorferi by the classical pathway are not clear. To address this question, we infected C1qa-/- mice, which cannot assemble the C1 complex and thus fail to activate the classical pathway, with B. burgdorferi sensu stricto strain B31. Using bioluminescent in vivo imaging, we found that C1qa-/- mice harbored more B. burgdorferi following 10 days of infection relative to their isogenic C57BL/6 parent. Quantitative PCR (qPCR) demonstrated that C1qa-/- mice harbored significantly more B. burgdorferi than parent mice did within lymph nodes, skin, heart, and joints. The increased B. burgdorferi load in C1qa-/- mice was observed at 21 and 28 days of infection, consistent with the classical pathway promoting complement-dependent, antibody-mediated killing following the development of a B. burgdorferi-specific humoral immune response. In addition, circulating borrelial-specific IgM was higher in C1qa-/- mice relative to their parent mouse strain and did not decrease at 21 and 28 days post infection, indicating that IgG class switching was delayed in C1qa-/- mice. At day 28, both Borrelia-specific IgG1 and IgG3 levels were higher in infected C1qa-/- mice but that these antibodies were not sufficient to control borrelial infection in the absence of the classical pathway. Furthermore, the lack of C1q also altered the balance of the Th1/Th2 response, as both circulating Th1 (MIP-1a, IL-2, IL-12 and TNFa), Th2 (IL-4, IL-10, MCP-1), and Th17 (IL-17) cytokines were elevated in infected C1qa-/- mice. These data imply that C1q and the classical pathway play important roles in controlling borrelial infection via antibody and complement-dependent killing, as well as altering both antibody maturation processes and the T cell response following exposure to infectious B. burgdorferi.